Architecture for residential care and ageing communities spaces for dwelling and healthcare - Gromark, Sten; Andersson, Björn, 1952 April 23- (London : Routledge, 2020)
Architecture for Residential Care and Ageing Communities confronts urgent architectural design challenges within residential innovation, ageing communities and healthcare environments. The increasing and diversified demands on the housing market today call for alterability and adaptability in long term solutions for new integrated ways of residing. Meanwhile, an accentuated ageing society requires new residential ways of living, combining dignity, independence and appropriate care. Concurrently, profound changes in technical conditions for home healthcare require rethinking healing environments. This edited collection explores the dynamics between these integrated architectural and caring developments and intends to envision reconfigured environmental design patterns that can significantly enhance new forms of welfare and ultimately, an improved quality of life. This book identifies, presents, and articulates new qualities in designs, in caring processes, and healing atmospheres, thereby providing operational knowledge developed in close collaboration with academics, actors and stakeholders in architecture, design, and healthcare. This is an ideal read for those interested in health promotivesituations of dwelling, ageing and caring.
OCLC-licensed vendor bibliographic record.
Keywords: Domestic architecture for older people; Barrier-free design for older people; Housing and health; Health promotion; ARCHITECTURE / Criticism; HEALTH & FITNESS / Healthy Living; ARCHITECTURE / Domestic